MicroRNA-322 (miR-322) and Its Target Protein Tob2 Modulate Osterix (Osx) mRNA Stability - Gámez, Beatriz (American Society for Biochemistry and Molecular Biology, 2013)
Osteogenesis depends on a coordinated network of signals and transcription factors such as Runx2 and Osterix. Recent evidence indicates that microRNAs (miRNAs) act as important post-transcriptional regulators in a large number of processes, including osteoblast differentiation. In this study, we performed miRNA expression profiling and identified miR-322, a BMP-2-down-regulated miRNA, as a regulator of osteoblast differentiation. We report miR-322 gain- and loss-of-function experiments in C2C12 and MC3T3-E1 cells and primary cultures of murine bone marrow-derived mesenchymal stem cells. We demonstrate that overexpression of miR-322 enhances BMP-2 response, increasing the expression of Osx and other osteogenic genes. Furthermore, we identify Tob2 as a target of miR-322, and we characterize the specific Tob2 3′-UTR sequence bound by miR-322 by reporter assays. We demonstrate that Tob2 is a negative regulator of osteogenesis that binds and mediates degradation of Osx mRNA. Our results demonstrate a new molecular mechanism controlling osteogenesis through the specific miR-322/Tob2 regulation of specific target mRNAs. This regulatory circuit provides a clear example of a complex miRNA-transcription factor network for fine-tuning the osteoblast differentiation program.